2004
DOI: 10.1262/jrd.50.323
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of Goat 20.ALPHA.-Hydroxysteroid Dehydrogenase cDNA

Abstract: Abstract. 20α-Hydroxysteroid dehydrogenase (20α-HSD), which catalyzes the conversion of progesterone to its inactive form 20α-dihydroprogesterone, is expressed in murine placenta and has been suggested to play roles in maintaining pregnancy. To understand the role of 20α-HSD during pregnancy in the goat, as a first step, cloning and sequencing of 20α-HSD cDNA were performed. The full nucleotide sequence of 20α-HSD cDNA was determined on samples obtained from the corpus luteum at the luteal phase of the estrous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 26 publications
2
15
1
Order By: Relevance
“…This is consistent, at least partially, with previous reports showing the presence of mRNA [9,10,12,21,22], protein [8] and the activity [8,11] of 20α-HSD in the placenta and/or uterus of several mammalian species. The expression of 20α-HSD in the intrauterine tissue in goats was especially prominent in the latter half of pregnancy, when the maternal serum progesterone levels were high.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This is consistent, at least partially, with previous reports showing the presence of mRNA [9,10,12,21,22], protein [8] and the activity [8,11] of 20α-HSD in the placenta and/or uterus of several mammalian species. The expression of 20α-HSD in the intrauterine tissue in goats was especially prominent in the latter half of pregnancy, when the maternal serum progesterone levels were high.…”
Section: Discussionsupporting
confidence: 92%
“…We have also shown that bacterially expressed protein using cloned goat 20α-HSD cDNA indeed possesses 20α-HSD activity [10]. In addition, we detected expression of 20α-HSD mRNA in the goat placenta, but not in the corpus luteum, liver, spleen or adrenal gland, at day 90 of pregnancy by means of RT-PCR [10].…”
mentioning
confidence: 68%
See 3 more Smart Citations